Issues and Challenges in Open and Distance e-Learning: Perspectives from the Philippines - Arinto, Patricia Brazil (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Rapid advances in information and communications technology in the digital age have brought about significant changes in the practice of distance education (DE) worldwide. DE practitioners in the Philippines’ open university have coined the term ‘open and distance e-learning’ (ODeL) to refer to the new forms of DE, which are characterised by the convergence of an open learning philosophy, DE pedagogies, and e-learning technologies. This paper discusses the issues and challenges that ODeL poses for the Philippines’ open university from the point of view of the institution’s leading ODeL practitioners. The paper concludes with a discussion of the policy development and administrative changes required to support innovative teaching practice across the institution. The findings and conclusions are relevant for other institutions in the same stage of ODeL development.